Is the ASA Score in Geriatric Hip Fractures a Predictive Factor for Complications and Readmission? - G. Kastanis; A. Topalidou; K. Alpantaki; M. Rosiadis; K. Balalis (Scientifica)
Hip fractures are the second cause of hospitalization in geriatric patients. The American Society of Anesthesiologists (ASA) classification scheme is a scoring system for the evaluation of the patients’ health and comorbidities before an operative procedure. The purpose of this study was to determine whether the ASA score is a predictive factor for perioperative and postoperative complications and a cause of readmission of geriatric patients with hip fractures. The study included 198 elderly patients. The mean values of hospitalization were 6.4±2.1 days for the patients with ASA II, 10.4±3.4 days for the patients with ASA III, and 13.5±4.4 days for the patients with ASA IV. The patients with ASA II exhibited minor complications, while patients with ASA III presented cutaneous ulcer and respiratory dysfunction. Five patients with ASA IV had pulmonary embolism, two patients had myocardial infarction, and three patients died. The ASA score seems to have direct correlation with multiple factors, such as the hospitalization days, the severity of the complications, and the total hospitalization costs. The treatment of geriatrics hip fractures in patients with a high ASA score requires a multidisciplinary approach and a special assessment in order to decrease postoperative morbidity and mortality and offer optimal functionality.